Intervention and regulation effect of Haematococcus pluvialis extract on blood glucose and lipid of diabetic mice - Huang Heru; Wang Shanshan; Ni Xiaofeng; Chen Riping; Zhang Jiali; Chen Yixiang; Shen Shengrong (浙江大学学报. 农业与生命科学版, 2015)
Diabetes was generally recognized as a critical issue in global public health, and has become the third noninfectious disease after angiocardiopathy and cancer. So far, the combination of applying insulin and controlling diet, as well as changing the way of living were the major therapeutic method for treating diabetes. Recently, the adjuvant therapy of natural extracts has been the research highlight in this field.To observe the intervention effect of Haematococcus pluvialis extract on blood glucose tolerance, insulin tolerance, lipid adjustment and the possible functional mechanism of improving diabetic patients' condition, the diabetic mouse models were induced by alloxan through intraperitoneal injection, and given by gavage with different doses of H. pluvialis extract for 28 days. The contents of fasting blood glucose and their body masses were detected at 7-day intervals. The capability of blood glucose tolerance and insulin tolerance was measured during later period of administration. Meanwhile, the contents of triacylglycerol (TG), serum total cholesterol (TC), high density lipoprotein cholesterol (HDL-C) and low density lipoprotein cholesterol (LDL-C) were detected.After modeling, the mice had dark and messy hair, and the typical diabetic symptoms including polydipsia, polyphagia and polyuria along with significant mass loss. Compared with the model group, by giving different doses of H. pluvialis extract in 28 d for experimental groups, the high, middle and low dose groups had statistically significant differences between the body masses and blood glucose contents, respectively (P<0.01, P<0.05, P<0.05). The difference between high dose group and model group was most evident. During the experiment of blood glucose tolerance, the blood glucose level of each group reached the peak in 30 min of glucose loading. The glucose levels appeared downtrend after 30 min, of which the high dose group and middle dose group were much lower than the model group in 120 min (P<0.01). In the insulin experiment, after injecting 0.8 U/kg insulin for 15 min, the blood glucose level of high dose group reduced by 20.9% compared with the basic level, while the low dose group only reduced by 0.6%. Three dose groups had the lowest blood glucose levels which reduced by 53.6%, 23.9% and 17.9% respectively in 90 min, while the model group reduced by 5.3%. The blood glucose increased in 120 min; however, the level in the high dose group of H. pluvialis extract was still much lower than that of model group (P<0.01). The TC, TG and LDL-C contents of the high dose group of H. pluvialis extract were much lower than the model group, which were statistically significant differences (P< 0.05, P<0.01, P<0.05).Haematococcus pluvialis extract has remarkable effect of decreasing blood glucose level, relieving the symptoms of polydipsia, polyphagia, polyuria and mass loss, improving the glucose tolerance and insulin tolerance, increasing the utilization of glucose and regulating blood lipid level on diabetic mice. However, it has no effect on the blood glucose and lipids of normal mice. Among the three dose groups, the high dose group (8 g/kg) has the best effect.